Students’ Anxieties Toward Research Proposal Seminar - Martha Kumala; Yuliana Dg. Macora; Sardi Sardi (Sintuwu Maroso Journal of English Teaching, 2023)
This study aims to determine the level and factors of the student anxiety towards seminar proposal. This type of research is qualitative research. The sample in this study is 14 students of 8th semester atAt English Language Education Study Program of Sintuwu Maroso University who were conducted proposal and undergraduate thesis seminars. The data are collected through questionnaires and interviews. The data are scored by using Zung’s Anxiety Scale, then they are analysed by using Ernawati and Fatma’s (2012) theory ofinfluence factor of anxiety and collaborated with Horwitz’ (2010) theory about foreign language anxiety factor.The results showed that all students experienced anxiety which is divided into three levels, namely severe anxiety experienced by 3 students (21%), moderate anxiety experienced by 6 students (43%), and normal anxiety experienced by 5 students (36%). While the factors that influence the anxiety are internal factors (shyness, lack of confidence, and mindset), external factors (embarrassment and lack of preparation), communication anxiety, exam anxiety and fear of negative evaluation.